EDUCATION AND TEA TRIBE COMMUNITY WOMEN- A CASE STUDY IN DIBRUGARH DISTRICT OF ASSAM - Saikia, Jutika (International Journal of Psychosocial Rehabilitation, 2020)
Education is an instrument that can change the status of women. The knowledge that is attained through education helps open doors to a lot of opportunities for better prospects in career growth. But unfortunately in Assam still a very large section of people especially women are deprived of getting education. Poverty is the greatest hindrance for attainment of education among women. In Assam the tea tribes are one of the community which is still backward in terms of education despite of various effort taken by the government in the field of education. This paper makes an attempt to highlight the status of education of tea worker’s women, their interest for education, their children status of education and also the various problem faced by them in continuation of education of their children after the primary education